The Association of Liver Enzymes With Acute Cholecystitis Diagnosed Using the Tokyo Criteria in the Eastern Region of Saudi Arabia: A Retrospective Case‐Control Study - Mohammed Y. Alessa; Jawad S. Alnajjar; Mohammed A. Almarzooq; Mohammed A. AlSharit; Sarah Talal AlFares; Ahmed E. Alamin; Zuhair Yousef Aljomeah; Loai S. Albinsaad (Health Science Reports)
ABSTRACT Background Acute cholecystitis, an inflammation of the gallbladder, is often triggered by gallstones but can also result from ischemia, motility issues, chemical harm, and microbial infections. This condition can present with fever, nausea, right upper quadrant pain, and tenderness, influenced by various risk factors including age, gender, genetics, obesity, diet, and lifestyle. Aim This retrospective case‐control study investigates the relationship between liver enzymes and acute cholecystitis in patients diagnosed based on Tokyo criteria in Alahsa, Saudi Arabia, from April 2016 to December 2023. Methods The study included 504 participants, with 249 cases of acute cholecystitis and 255 controls without cholecystitis, collected from King Fahad Hospital's medical records. Inclusion criteria were patients above 18 years old diagnosed with acute cholecystitis and availability of liver enzyme data. Data were analysed using SPSS version 21, employing descriptive analysis, Pearson Chi‐Square test, Kruskal‐Wallis test, box‐plot visualization, Spearman correlation analysis, and ROC curve analysis. Results The mean age was similar between cases (39.9 ± 15.3 years) and controls (40.1 ± 13.9 years). Significant differences were found in gender distribution and BMI. ALT and ALP levels were significantly higher in cases compared to controls (p = 0.002 and p = 0.001, respectively). The WBC count was also significantly higher in cases (p = 0.001). ROC curve analysis indicated that ALT and ALP had good discriminant ability to predict acute cholecystitis. Multiple hierarchical logistic regression showed that higher levels of ALT and ALP were significant predictors for acute cholecystitis, with adjusted odds ratios of 1.21 and 1.24, respectively. Conclusion Elevated ALT and ALP levels are significant predictors of acute cholecystitis, demonstrating the importance of liver enzymes in the diagnosis and management of this condition. The findings suggest that integrating liver enzyme measurements with Tokyo criteria can enhance diagnostic accuracy and improve healthcare outcomes for patients with acute cholecystitis.